Integrated Delivery of Quality, Safety and Environment through Road Sector Procurement: The Case of Public Sector Agencies in Ghana - Mahamadu, Abdul Majeed; Mahdjoubi, Lamine; Booth, Colin; Fewings, Peter (Penerbit Universiti Sains Malaysia, 2015)
Poor quality, safety and environmental (QSE) performance within Ghana's road sector has been cited as a major challenge in the procurement of infrastructure. This study evaluates the applicability and level of integrated consideration of QSE in the delivery of roads through procurement by public sector agencies in Ghana. Integrated delivery is explored on the basis of theoretical and empirical evidence of an existing synergistic relationship among QSE in the management and delivery of projects. A mixed methodological design was adopted to investigate two public road agencies through a questionnaire survey and interviews of technical staff with procurement responsibilities. This was done concurrently with soliciting professional perspectives on the subject. Procurement is widely regarded as paramount to the delivery of better QSE in the Ghana road sector. However, the level of synergistic consideration is low, which is attributable to an over-reliance on traditional procurement arrangements as a result of non-supportive local procurement regulatory frameworks. It is further established that a general lack of know-how and experience in the use of modern and integrated procurement arrangements prevent effective management and realisation of QSE beyond the current focus on time and cost through procurement processes within public road sector agencies.